2016
DOI: 10.1177/1591019916668842
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative assessment of parent vessel and distal intracranial hemodynamics following pipeline flow diversion

Abstract: Background Pipeline embolization devices (PEDs) are commonly used for endovascular treatment of cerebral aneurysms but can be associated with delayed ipsilateral intraparenchymal hemorrhage. Although intra-aneurysmal hemodynamic changes have been studied, parent vessel and intracranial hemodynamics after PED use are unknown. We examine the impact of flow diversion on parent artery and distal intracranial hemodynamics. Method Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(41 citation statements)
references
References 14 publications
1
40
0
Order By: Relevance
“…The presence of an aneurysm might modify the physiological hemodynamic patterns in the parent artery, which may, in turn, affect the cellular function in the surrounding vasculature. Furthermore, FD treatment in the internal carotid artery has shown to alter the hemodynamics by increasing flow velocities and wall shear stress, while lowering resistance in the ipsilateral middle cerebral artery 19. Further studies are needed to substantiate the mechanism for the changes in contractility of the distal vessel wall and its potential pathophysiological impact.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of an aneurysm might modify the physiological hemodynamic patterns in the parent artery, which may, in turn, affect the cellular function in the surrounding vasculature. Furthermore, FD treatment in the internal carotid artery has shown to alter the hemodynamics by increasing flow velocities and wall shear stress, while lowering resistance in the ipsilateral middle cerebral artery 19. Further studies are needed to substantiate the mechanism for the changes in contractility of the distal vessel wall and its potential pathophysiological impact.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complex flow pattern, deployment of a flow diverter to the aneurysm might result in unfavorable outcome. Shakur et al as well as other authors had reported that after PED placement, the hemodynamics in distal arteries will be disrupted and contribute to delayed ipsilateral intraparenchymal hemorrhage [21,22]. In our Case NO.…”
Section: Discussionmentioning
confidence: 48%
“…In addition, once aneurysms or stenoses have formed, the pathology may cause further changes to local and more significantly to the global blood flow distribution patterns. Adverse distal effects such as remote ipsilateral hemorrhage may be detected and pinpointed with the proposed global hemodynamic analysis. The proposed parametric structured meshing technique extends rigorous CFD analysis from a single site to large portions of the cerebrovascular network.…”
Section: Discussionmentioning
confidence: 99%